Biomass-based hard carbon negative electrode material, preparation method thereof and sodium ion battery

By performing multi-step treatment of the biomass hardcoal precursor, including precharging, pickling and silane coupling agent doping, biomass-based hardcoal negative electrode materials with high specific capacity and excellent kinetic properties, solving the shortcomings of existing materials in specific capacity and kinetic properties.

CN119591083AActive Publication Date: 2025-03-11GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411789342.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The biomass-based hard carbon anode materials of existing sodium ion batteries have shortcomings in specific capacity, kinetic performance and compaction density, making it difficult to reach the level of lithium ion batteries.

Method used

By coarsely crushing, pre-charging, crushing, pickling, washing and drying of the biomass hardcarbon precursor, then adding silane coupling agent and phosphorus-containing dopant to the water for mixing, stirring and drying, and finally carbonizing and screening, a biomass-based hardcarbon negative electrode material with suitable compaction density and specific surface area was prepared.

Benefits of technology

This method effectively improves the specific capacity, first-time Coulomb efficiency and rate performance of biomass-based hard carbon anode material, making it perform better in sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591083A_ABST
    Figure CN119591083A_ABST
Patent Text Reader

Abstract

The invention provides a biomass-based hard carbon negative electrode material, a preparation method thereof and a sodium ion battery, and relates to the technical field of sodium ion battery negative electrode materials. The preparation method of the biomass-based hard carbon negative electrode material comprises the following steps: S1, carrying out coarse crushing and pre-carbonization on a biomass hard carbon precursor to obtain a pre-carbonized material; s2, crushing, pickling, washing and drying the pre-carbonized material to obtain a purified material; s3, adding a silane coupling agent into water, carrying out primary mixing and stirring to obtain a first solution, adding the purified material into the first solution, carrying out secondary mixing and stirring to obtain a second solution, adding a phosphorus-containing dopant into the second solution, carrying out tertiary mixing and stirring, and drying to obtain a first precursor; and S4, carbonizing and screening the first precursor. The biomass-based hard carbon negative electrode material prepared by the invention has proper compaction density and specific surface area, and can effectively improve the specific capacity, the first coulombic efficiency and the rate capability of a sodium ion battery when being used in the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a biomass-based hard carbon negative electrode material and a preparation method thereof and a sodium ion battery. Background Art

[0002] As a common secondary battery, lithium-ion batteries have been widely used in 3C, power batteries, energy storage and other fields. However, with the continuous increase in production, the disadvantages of uneven distribution of lithium resources, insufficient reserves and high costs have become increasingly exposed. The huge contradiction between supply and demand and repeated price fluctuations have become a dark cloud hanging over the entire industrial chain. At the same time, with the continuous breakthrough of technical barriers, especially the continuous improvement of hard carbon negative electrodes with excellent sodium storage performance, sodium-ion batteries have returned to the public eye, and their outstanding cost advantages have made them a hot alternative to lithium-ion batteries.

[0003] Sodium-ion batteries and lithium-ion batteries are both "rocking chair batteries" that can achieve charge transfer by the release and embedding of sodium ions or lithium ions at the positive and negative electrodes during charging and discharging. In addition to cost advantages, sodium-ion batteries have the advantages of high safety performance and excellent high and low temperature performance, but the energy density and cycle life are still difficult to reach the level of lithium-ion batteries. At present, the precursors of hard carbon negative electrode materials for sodium-ion batteries mainly include biomass, synthetic polymers and fossil fuels. Among them, biomass-based hard carbon materials are regarded as cutting-edge negative electrode materials with great development prospects due to their unique natural microstructure, high material purity, functional diversity, and easy structural regulation. However, compared with polymers and fossil fuels, specific capacity, kinetic performance, and compaction density are still the shortcomings of biomass hard carbon.

[0004] Therefore, there is an urgent need for a biomass-based hard carbon negative electrode material and a preparation method thereof and a sodium ion battery to address the deficiencies of the prior art. Summary of the invention

[0005] The object of the present invention is to provide a biomass-based hard carbon negative electrode material and a preparation method thereof and a sodium ion battery. The biomass-based hard carbon negative electrode material of the present invention has a suitable compaction density and specific surface area, and can be used in a sodium ion battery to effectively improve its specific capacity, first coulombic efficiency and rate performance.

[0006] To achieve the above object, the first aspect of the present invention provides a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0007] S1: coarsely crushing and pre-carbonizing the biomass hard carbon precursor to obtain a pre-carbonized material;

[0008] S2 crushes the pre-carbonized material, pickles it, washes it with water and dries it to obtain a purified treated material;

[0009] S3: adding a silane coupling agent to water, mixing and stirring once to obtain a first solution, adding a purified material to the first solution, mixing and stirring twice to obtain a second solution, adding a phosphorus-containing dopant to the second solution, mixing and stirring three times, and then drying to obtain a first precursor;

[0010] S4 carbonizes and screens the first precursor.

[0011] Compared with the prior art, the present invention firstly crushes the biomass hard carbon precursor and pre-carbonizes it to obtain a pre-carbonized material, so as to effectively remove the moisture and organic volatiles in the biomass, which is convenient for subsequent purification, doping and carbonization treatment; the pre-carbonized material is acid-washed to effectively remove the acid-soluble impurities contained therein to improve its purity, and at the same time, oxygen-containing functional groups can be introduced on the surface of the material during the acid-washing process, which is beneficial to the subsequent coating modification of the purified material by a silane coupling agent and a phosphorus-containing dopant; a silane coupling agent is added to water to form a first solution, and during the stirring and mixing process, the silane coupling agent can be hydrolyzed in water to form a silanol bond, and the purified material is added to the first solution and stirred to form a second solution, and during the stirring process, the silanol bond formed can react with the purified material. The oxygen-containing functional groups on the surface of the purified material form covalent bonds with strong bonding force, so that the silane coupling agent is uniformly and firmly loaded on the surface of the purified material. Finally, a phosphorus-containing dopant is added to the second solution to react with the organic functional groups of the silane coupling agent to form a stable chemical bond, thereby achieving a close combination and uniform coating of the purified material-silane coupling agent-phosphorus-containing dopant. The obtained first precursor is carbonized. During the carbonization process, the silane coupling agent is pyrolyzed into silane and finally decomposed into silicon element, which improves the specific capacity of the biomass-based hard carbon negative electrode material. The phosphorus-containing dopant can fill the pores on the surface of the material after carbonization and pyrolysis. At the same time, the introduction of phosphorus effectively improves the first coulomb efficiency and rate performance of the negative electrode material of the present invention. Therefore, the biomass-based hard carbon negative electrode material prepared by the preparation method of the present invention has a suitable compaction density and specific surface area, and can be used in sodium ion batteries to effectively improve its first coulomb efficiency and rate performance.

[0012] In some embodiments, the biomass hard carbon precursor is selected from at least one of coconut shell, bamboo, lignin, microcrystalline cellulose, starch and glucose, and the particle size Dv50 of the coarsely crushed material is 1 mm to 8 mm.

[0013] In some embodiments, the pre-carbonization is performed in an inert atmosphere, the pre-carbonization temperature is 400° C. to 700° C., and the holding time is 0.5 h to 10 h.

[0014] In some embodiments, the pulverizing method includes at least one of air flow milling, roller milling and mechanical milling, the particle size Dv 50 of the pulverized material is 4 μm to 10 μm, the drying temperature is 80° C. to 200° C., and the drying time is 2 h to 24 h.

[0015] In some embodiments, the acid washing comprises placing the pre-carbonized material in an acid solution and stirring and washing it at a stirring rate of 100 rpm to 200 rpm for 2 hours to 24 hours, the acid solution is selected from at least one of hydrochloric acid, nitric acid and hydrofluoric acid, the mass ratio of the acid solution to the pre-carbonized material is 0.2 to 5:1, the pH of the acid solution is 1 to 3, and the water washing comprises repeatedly washing the pre-carbonized material after the acid washing with water until the pH of the filtrate is greater than 2.

[0016] In some embodiments, the silane coupling agent is selected from at least one of KH-550, KH-560, A-187, XR-560, Si-902 and WD-50, the phosphorus-containing dopant is selected from at least one of triethyl phosphate, triphenylphosphine, tricresyl phosphate and dimethyl phosphate, and the mass ratio of the silane coupling agent, the purified treatment material and the phosphorus-containing dopant is 0.01~0.1:1~10:0.1~1.

[0017] In some embodiments, the stirring rate of the first mixing and stirring is 200rpm~300rpm, and the time of the first mixing and stirring is 0.5h~5h, the stirring rate of the second mixing and stirring is 300rpm~500rpm, and the time of the second mixing and stirring is 0.5h~5h, the stirring rate of the third mixing and stirring is 150rpm~300rpm, and the time of the third mixing and stirring is 1h~10h, the drying temperature is 50℃~200℃, and the drying time is 12h~48h.

[0018] In some embodiments, carbonization is carried out in an inert atmosphere, the carbonization heating rate is 1°C / min to 10°C / min, the carbonization temperature is 1000°C to 1600°C, the insulation time is 0.5h to 10h, and the mesh size of the sieve used for screening is 200 to 400 mesh.

[0019] A second aspect of the present invention provides a biomass-based hard carbon negative electrode material, which is prepared using the aforementioned method for preparing the biomass-based hard carbon negative electrode material.

[0020] A third aspect of the present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is the aforementioned biomass-based hard carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the biomass-based hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is the biomass-based hard carbon negative electrode material of the present invention. The preparation of the biomass-based hard carbon negative electrode material of the present invention comprises:

[0023] S1: coarsely crushing and pre-carbonizing the biomass hard carbon precursor to obtain a pre-carbonized material;

[0024] S2 crushes the pre-carbonized material, pickles it, washes it with water and dries it to obtain a purified treated material;

[0025] S3: adding a silane coupling agent to water, mixing and stirring once to obtain a first solution, adding a purified material to the first solution, mixing and stirring twice to obtain a second solution, adding a phosphorus-containing dopant to the second solution, mixing and stirring three times, and then drying to obtain a first precursor;

[0026] S4 carbonizes and screens the first precursor.

[0027] In S1, the biomass hard carbon precursor is selected from at least one of coconut shell, bamboo, lignin, microcrystalline cellulose, starch and glucose. In some technical schemes, the biomass hard carbon precursor is selected from coconut shell. In some technical schemes, the biomass hard carbon precursor is selected from coconut shell and bamboo. In some technical schemes, the biomass hard carbon precursor is selected from lignin. In some technical schemes, the biomass hard carbon precursor is selected from microcrystalline cellulose. In some technical schemes, the biomass hard carbon precursor is selected from starch. In some technical schemes, the biomass hard carbon precursor is selected from glucose. The use of biomass-based hard carbon precursors is low in cost and has the advantages of being renewable, abundant in source, low in price, and green and environmentally friendly.

[0028] The particle size Dv 50 of the biomass hard carbon precursor after coarse crushing is 1mm to 8mm. As an example, the particle size Dv 50 of the coarse crushed material can be, but is not limited to, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, and 8mm. Pre-carbonization is carried out in an inert atmosphere. The inert atmosphere is selected from at least one of nitrogen, helium, and argon. The pre-carbonization temperature is 400°C to 700°C. In some technical schemes, the pre-carbonization temperature is 420°C to 685°C. In some technical schemes, the pre-carbonization temperature is 465°C to 595°C. As an example, the pre-carbonization temperature can be, but is not limited to, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, and 700°C. The pre-carbonization insulation time is 0.5h to 10h. In some technical solutions, the pre-carbonization insulation time is 4h to 10h. In some technical solutions, the pre-carbonization insulation time is 5h to 8h. In some technical solutions, the pre-carbonization insulation time is 6h to 7h. As an example, the pre-carbonization insulation time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. Pre-carbonizing the biomass-based hard carbon precursor at 400℃ to 700℃ can effectively remove moisture and organic volatiles present in the biomass, increase the energy density and volume density of the biomass, and avoid the rapid volatilization of moisture and organic volatiles when carbonizing directly at high temperature, which affects its carbonization effect.

[0029] In S2, the pulverization method includes at least one of air flow milling, roller milling and mechanical milling. The particle size Dv 50 of the material after pulverization is 4μm to 10μm. As an example, the particle size Dv 50 of the material after pulverization can be but is not limited to 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm. The pulverized material is demagnetized to reduce the content of magnetic substances in the material and reduce the influence of the magnetic content on the electrochemical properties of subsequent biomass-based hard carbon negative electrode materials. The demagnetization can be specifically carried out in a demagnetizer.

[0030] The drying temperature is 80°C to 200°C. In some technical solutions, the drying temperature is 86°C to 195°C. In some technical solutions, the drying temperature is 90°C to 180°C. In some technical solutions, the drying temperature is 100°C. As an example, the drying temperature can be, but is not limited to, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C. The drying time is 2h to 24h. In some technical solutions, the drying time is 4h to 24h. In some technical solutions, the drying time is 6h to 20h. As an example, the drying time can be but is not limited to 2h, 4h, 6h, 8h, 10h, 11h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.

[0031] Pickling includes placing the pre-carbonized material in an acid solution and stirring and washing it at a stirring rate of 100rpm to 200rpm for 2h to 24h. As an example, the stirring rate can be but is not limited to 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm, 200rpm. The stirring and washing time can be but is not limited to 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 12h, 14h, 16h, 18h, 19h, 20h, 22h, 24h. The acid solution is selected from at least one of hydrochloric acid, nitric acid and hydrofluoric acid. In some technical solutions, the acid solution is hydrochloric acid, in some technical solutions, the acid solution is nitric acid, and in some technical solutions, the acid solution is hydrofluoric acid. The mass ratio of the acid solution to the pre-carbonized material is 0.2 to 5:1. In some technical solutions, the mass ratio of the acid solution to the pre-carbonized material is 1 to 5:1. In some technical solutions, the mass ratio of the acid solution to the pre-carbonized material is 2 to 5:1. As an example, the mass ratio of the acid solution to the pre-carbonized material can be, but not limited to, 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1. The pH of the acid solution is 1 to 3. As an example, the pH of the acid solution can be, but not limited to, 1, 2, and 3. In the pickling process, in addition to effectively removing impurities present in the pre-oxidized material, it can also be oxidized to introduce oxygen-containing functional groups. Water washing includes repeatedly washing the pre-carbonized material after pickling until the pH of the filtrate is greater than 2, as an example. The pH of the filtrate after water washing can be, but not limited to, 2.5, 3, 4, 5, 6, and 7.

[0032] In S3, the silane coupling agent is selected from at least one of KH-550, KH-560, A-187, XR-560, Si-902 and WD-50, and the phosphorus-containing dopant is selected from at least one of triethyl phosphate, triphenylphosphine, tricresyl phosphate and dimethyl phosphate. The mass ratio of the silane coupling agent, the purified material and the phosphorus-containing dopant is 0.01-0.1:1-10:0.1-1. In some technical solutions, the mass ratio of the silane coupling agent, the purified material and the phosphorus-containing dopant is 0.3-4:1-8:1. As an example, the mass ratio of the silane coupling agent, the purified material and the phosphorus-containing dopant can be, but is not limited to, 0.01:1:1, 0.05:1:1, 0.1:1:1, 0.01:2:1, 0.05:2:1, 0.1:2:1, 0.01:4:1, 0.05:4:1, 0.1:4:1, 0.01:6:1, 0.05:6:1, 0.1:6:1, 0.01:8:1 , 0.05:8:1, 0.1:8:1, 0.01:10:1, 0.05:10:1, 0.1:10:1, 0.01:1:0.5, 0.05:1:0.5, 0.1:1:0.5, 0.01:2:0.5, 0.05:2:0.5, 0.1:2:0.5, 0.01:4:0.5, 0.05:4:0.5, 0.1:4:0.5, 0.0 1:6:0.5, 0.05:6:0.5, 0.1:6:0.5, 0.01:8:0.5, 0.05:8:0.5, 0.1:8:0.5, 0.01:10:0.5, 0.05:10:0.5, 0.1:10:0.5, 0.01:1:0.2, 0.05:1:0.2, 0.1:1:0.2, 0.01:2:0.2, 0.05:2 :0.2, 0.1:2:0.2, 0.01:4:0.2, 0.05:4:0.2, 0.1:4:0.2, 0.01:6:0.2, 0.05:6:0.2, 0.1:6:0.2, 0.01:8:0.2, 0.05:8:0.2, 0.1:8:0.2, 0.01:10:0.2, 0.05:10:0.2, 0.1:10:0.2. The present invention firstly dissolves a silane coupling agent in water to form a first solution, wherein the silane coupling agent can form a silanol bond in water, and then places a purified material obtained after acid washing, water washing and drying in the first solution for mixing and stirring to form a second solution. During the mixing and stirring process, oxygen-containing functional groups on the surface of the purified material can react with the silanol bond to form a connecting bond with a strong bonding effect so that the silane coupling agent is evenly loaded on the surface of the purified material. Then, a phosphorus-containing dopant is added to the second solution for mixing and stirring, and the phosphorus-containing dopant is bonded to the silane coupling agent to form a tightly connected purified material-silane coupling agent-phosphorus-containing dopant structure, i.e., a first precursor.

[0033] The stirring rate of the first mixing and stirring is 200rpm~300rpm. As an example, the stirring rate of the first mixing and stirring can be, but not limited to, 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm. The stirring time of the first mixing and stirring is 0.5h~5h. As an example, the stirring time of the first mixing and stirring can be, but not limited to, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h. The stirring rate of the second mixing and stirring is 300rpm~500rpm. As an example, the stirring rate of the second mixing and stirring can be, but not limited to, 300rpm, 320rpm, 340rpm, 360rpm, 380rpm, 400rpm, 420rpm, 440rpm, 460rpm, 480rpm, 500rpm. The stirring time of the secondary mixing and stirring is 0.5h~5h. As an example, the stirring time of the secondary mixing and stirring can be, but is not limited to, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h. The stirring rate of the tertiary mixing and stirring is 150rpm~300rpm, and the time of the tertiary mixing and stirring is 2h~10h. As an example, the stirring rate of the tertiary mixing and stirring can be, but is not limited to, 150rpm, 170rpm, 200rpm, 220rpm, 250rpm, 280rpm, 300rpm. The stirring time of the tertiary mixing and stirring can be, but is not limited to, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h. The drying temperature is 50°C to 200°C. As an example, the drying temperature can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 120°C, 140°C, 160°C, 180°C, and 200°C. The drying time is 12h to 48h. As an example, the drying time can be, but is not limited to, 24h to 48h. The drying time can be, but is not limited to, 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, and 48h.

[0034] In S4, carbonization is carried out in an inert atmosphere, and the inert atmosphere is selected from at least one of nitrogen, argon and helium. The heating rate of carbonization is 1°C / min to 10°C / min. In some technical schemes, the heating rate of carbonization is 2°C / min to 8°C / min. In some technical schemes, the heating rate of carbonization is 3°C / min to 7°C / min. In some technical schemes, the heating rate of carbonization is 5°C / min. As an example, the heating rate of carbonization can be but is not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The temperature of carbonization is 1000°C to 1600°C. In some technical schemes, the temperature of carbonization is 1100°C to 1400°C. In some technical schemes, the temperature of carbonization is 1180°C to 1360°C. As an example, the carbonization temperature can be, but is not limited to, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C. The carbonization insulation time is 0.5h to 10h. In some technical solutions, the carbonization insulation time is 3h to 8h. In some technical solutions, the carbonization insulation time is 3h to 6h. As an example, the carbonization insulation time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. The mesh size of the sieve used for screening is 200 mesh to 400 mesh. In some technical solutions, the mesh size of the sieve used for screening is 325 mesh to 400 mesh. As an example. The mesh size of the sieve used for screening can be but is not limited to 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 260 mesh, 270 mesh, 280 mesh, 290 mesh, 300 mesh, 315 mesh, 325 mesh, 335 mesh, 345 mesh, 355 mesh, 365 mesh, 375 mesh, 385 mesh, 395 mesh, and 400 mesh.

[0035] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0036] Example 1

[0037] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0038] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0039] S2: The pre-carbonized material is ground by air jet mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, and then the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0040] S3: 1 g of KH-550 was added to 100 g of deionized water and stirred at 200 rpm for 1 h to obtain a first solution, 100 g of the purified material was added to the first solution and stirred at 300 rpm for 1 h to obtain a second solution, 10 g of triethyl phosphate was added to the second solution and stirred at 300 rpm for 2 h, and then the reaction solution was placed in an oven at 100° C. to dry to obtain a first precursor;

[0041] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0042] Figure 1 The SEM image of the biomass-based hard carbon negative electrode material prepared in this example is shown.

[0043] Example 2

[0044] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0045] S1: 200 g of bamboo was roughly chopped to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0046] S2: The pre-carbonized material is ground by air jet mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, and then the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0047] S3: 1 g of KH-550 was added to 100 g of deionized water and stirred at 200 rpm for 1 h to obtain a first solution, 100 g of the purified material was added to the first solution and stirred at 300 rpm for 1 h to obtain a second solution, 18 g of triethyl phosphate was added to the second solution and stirred at 300 rpm for 2 h, and then the reaction solution was placed in an oven at 100° C. to dry to obtain a first precursor;

[0048] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0049] Example 3

[0050] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0051] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0052] S2: The pre-carbonized material is ground by air flow mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered to obtain an acid-washed material, the acid-washed material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100° C. oven to dry to obtain a purified treated material;

[0053] S3: 1 g of KH-550 was added to 100 g of deionized water and stirred at 200 rpm for 1 h to obtain a first solution, 100 g of the purified material was added to the first solution and stirred at 300 rpm for 1 h to obtain a second solution, 10 g of dimethyl phosphate was added to the second solution and stirred at 300 rpm for 2 h, and then the reaction solution was placed in an oven at 100° C. to dry to obtain a first precursor;

[0054] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0055] Example 4

[0056] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0057] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0058] S2: The pre-carbonized material is ground by air flow mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, and then the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0059] S3: 0.6 g KH-550 was added to 100 g deionized water and stirred at 200 rpm for 1 h to obtain a first solution, 100 g purified material was added to the first solution and stirred at 300 rpm for 1 h to obtain a second solution, 10 g triethyl phosphate was added to the second solution and stirred at 300 rpm for 2 h, and then the reaction solution was placed in an oven at 100° C. to dry to obtain a first precursor;

[0060] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0061] Example 5

[0062] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0063] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0064] S2: The pre-carbonized material is ground by air jet mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, and then the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0065] S3: 1 g of KH-550 was added to 100 g of deionized water and stirred at 200 rpm for 1 h to obtain a first solution, 100 g of the purified material was added to the first solution and stirred at 300 rpm for 1 h to obtain a second solution, 15 g of triethyl phosphate was added to the second solution and stirred at 300 rpm for 2 h, and then the reaction solution was placed in an oven at 100° C. to dry to obtain a first precursor;

[0066] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0067] Example 6

[0068] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0069] S1 500 g of bamboo was roughly chopped to a Dv 50 of 7 mm, and then placed in a tubular furnace and pre-carbonized at 480° C. for 6 h in a nitrogen atmosphere to obtain a pre-carbonized material;

[0070] S2: The pre-carbonized material is ground by air flow mill to a Dv 50 of 4 μm, 150 g of the ground pre-carbonized material is placed in 150 g of a hydrofluoric acid solution with a pH of 2, stirred and washed at a stirring rate of 180 rpm for 7 hours, and then positive pressure filtered, the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 6, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0071] S3: 1 g of A-187 was added to 100 g of deionized water and stirred at 245 rpm for 2 h to obtain a first solution, 100 g of the purified material was added to the first solution and stirred at 365 rpm for 3 h to obtain a second solution, 22 g of triethyl phosphate was added to the second solution and stirred at 250 rpm for 3 h, and then the reaction solution was placed in an oven at 100° C. and dried to obtain a first precursor;

[0072] S4: placing the first precursor in an atmosphere furnace, heating it to 1200°C at a heating rate of 5°C / min under a nitrogen atmosphere, and heat-treating it for 6 hours. After cooling to room temperature, the precursor was sieved through a 285-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0073] Comparative Example 1

[0074] This comparative example is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0075] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0076] S2: The pre-carbonized material is ground by air flow mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0077] S3: placing the purified material in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the material is sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0078] Comparative Example 2

[0079] This comparative example is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0080] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0081] S2: The pre-carbonized material is ground by air flow mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, and then the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0082] S3: adding 100 g of the purified material to 100 g of deionized water and stirring at 300 rpm for 1 h to obtain a first solution, adding 10 g of triethyl phosphate to the first solution and stirring at 300 rpm for 2 h, and then drying the reaction solution in an oven at 100° C. to obtain a first precursor;

[0083] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0084] Comparative Example 3

[0085] This embodiment is a method for preparing a biomass-based hard carbon negative electrode material, comprising:

[0086] S1: 200 g of coconut shells were roughly crushed to a Dv 50 of 5 mm, and then placed in a tube furnace and pre-carbonized at 550° C. for 4 h in an argon atmosphere to obtain a pre-carbonized material;

[0087] S2: The pre-carbonized material is ground by air jet mill to a Dv 50 of 5 μm, 150 g of the ground pre-carbonized material is placed in 300 g of a hydrochloric acid solution with a pH of 3, stirred and washed at a stirring rate of 150 rpm for 8 hours, and then positive pressure filtered, and then the acid-washed pre-carbonized material is repeatedly washed with water until the pH of the filtrate is 5.5, and finally placed in a 100°C oven to dry to obtain a purified treated material;

[0088] S3: adding 1 g of KH-550 to 100 g of deionized water and stirring at 200 rpm for 1 h to obtain a first solution, adding 100 g of the purified material to the first solution and stirring at 300 rpm for 1 h, and then drying the reaction solution in an oven at 100° C. to obtain a first precursor;

[0089] S4: placing the first precursor in an atmosphere furnace, heating it to 1300°C at a heating rate of 2°C / min under an argon atmosphere, and heat-treating it for 5 hours. After cooling to room temperature, the precursor was sieved through a 325-mesh sieve to obtain a biomass-based hard carbon negative electrode material.

[0090] The button cell was assembled using the biomass-based hard carbon negative electrode material prepared in Examples 1 to 6 and Comparative Examples 1 to 3 as the negative electrode material, metallic sodium as the positive electrode material, glass fiber as the separator, and 1 mol / L NaClO4 (PC+5% FEC) as the electrolyte. The positive electrode was charged and discharged in the voltage range of 2.0-4.0V at a current density of 0.1C, and then the rate performance was tested at a current density of 1C. The test results are shown in Table 1.

[0091] Among them, the specific surface area was obtained by using the nitrogen adsorption / desorption isotherm of the material using a Micromeritics ASAP 2460 analyzer, and its specific surface area was calculated by the BET method;

[0092] The compaction density was measured using a UTM7305 battery powder compaction density tester.

[0093] Table 1 Performance test results of Examples 1 to 6 and Comparative Examples 1 to 3

[0094]

[0095] It can be seen from the test results in Table 1, specifically see Examples 1 to 6 and Comparative Examples 1 to 3, that the biomass-based hard carbon negative electrode material prepared by the preparation method of the present invention has a more suitable compaction density and specific surface area, and its comprehensive performance of specific capacity, first coulombic efficiency and rate is better.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a biomass-based hard carbon negative electrode material, characterized in that: include: S1: coarsely crushing and pre-carbonizing the biomass hard carbon precursor to obtain a pre-carbonized material; S2: crushing, acid washing, water washing and drying the pre-carbonized material to obtain a purified material; S3: adding a silane coupling agent to water, mixing and stirring once to obtain a first solution, adding the purified material to the first solution, mixing and stirring twice to obtain a second solution, adding a phosphorus-containing dopant to the second solution, mixing and stirring three times, and drying to obtain a first precursor; S4: carbonizing and screening the first precursor.

2. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The biomass hard carbon precursor is selected from at least one of coconut shell, bamboo, lignin, microcrystalline cellulose, starch and glucose, and the particle size Dv 50 of the coarsely crushed material is 1 mm to 8 mm.

3. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The pre-carbonization is carried out in an inert atmosphere, the pre-carbonization temperature is 400° C. to 700° C., and the heat preservation time is 0.5 h to 10 h.

4. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The pulverizing method includes at least one of air flow mill, roller mill and mechanical mill. The particle size Dv 50 of the pulverized material is 4 μm to 10 μm. The drying temperature is 80° C. to 200° C. and the drying time is 2 h to 24 h.

5. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The acid washing comprises placing the pre-carbonized material in an acid solution and stirring and washing it at a stirring rate of 100 rpm to 200 rpm for 2 hours to 24 hours, the acid solution is selected from at least one of hydrochloric acid, nitric acid and hydrofluoric acid, the mass ratio of the acid solution to the pre-carbonized material is 0.2 to 5:1, the pH of the acid solution is 1 to 3, and the water washing comprises repeatedly washing the pre-carbonized material after the acid washing with water until the pH of the filtrate is greater than 2.

6. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The stirring rate of the first mixing and stirring is 200rpm~300rpm, and the time of the first mixing and stirring is 0.5h~5h. The stirring rate of the second mixing and stirring is 300rpm~500rpm, and the time of the second mixing and stirring is 0.5h~5h. The stirring rate of the tertiary mixing and stirring is 150rpm~300rpm, and the time of the tertiary mixing and stirring is 1h~10h. The drying temperature is 50℃~200℃, and the drying time is 12h~48h.

7. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The silane coupling agent is selected from at least one of KH-550, KH-560, A-187, XR-560, Si-902 and WD-50, the phosphorus-containing dopant is selected from at least one of triethyl phosphate, triphenylphosphine, tricresyl phosphate and dimethyl phosphate, and the mass ratio of the silane coupling agent, the purified material and the phosphorus-containing dopant is 0.01-0.1:1-10:0.1-1.

8. The method for preparing a biomass-based hard carbon precursor negative electrode material according to claim 1, characterized in that: The carbonization is carried out in an inert atmosphere, the heating rate of the carbonization is 1°C / min to 10°C / min, the carbonization temperature is 1000°C to 1600°C, the insulation time is 0.5h to 10h, and the mesh number of the sieve used for screening is 200 to 400 meshes.

9. Biomass-based hard carbon negative electrode material, characterized in that: The biomass-based hard carbon negative electrode material is prepared by the method for preparing the biomass-based hard carbon negative electrode material according to any one of claims 1 to 8.

10. A sodium ion battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material is the biomass-based hard carbon negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material

    CN113381016A

  • Titanium niobate coated hard carbon composite material and preparation method thereof

    CN114094070A

  • Preparation method and application of high-energy-density hard carbon composite negative electrode material

    CN114583093A

  • High-capacity hard carbon fast-charging negative electrode material as well as preparation method and application thereof

    CN114695894A

  • Silicon-phosphorus co-doped hard carbon composite material and preparation method and application thereof

    CN114843480A